Spectrum of behavioural abnormalities in children with nephrotic syndrome in southwestern Nigeria (2015)
Nephrotic syndrome is a chronic childhood disease characterized by relapses and children with this condition tend to have behavioural problems associated with the disease. These behavioural problems are usually not anticipated in most resource limited settings and can be frightening thereby making the children and the care givers to be distressed. Seven children with nephrotic syndrome who developed various behavioural abnormalities while on admission were discussed. There were four girls and three boys with age range seven to fourteen years. The abnormal behaviours noted were visual and auditory hallucinations, inappropriate speech and behaviour, attempted suicide, attention seeking behaviour and social withdrawal. These behavioural abnormalities were related to prednisolone therapy in five of the children. Diagnosis made were psychosis and delirium while treatment given included counselling, Risperidone, Halloperidol, Diazepam and reduction or withdrawal of Prednisolone. Abnormal behaviour was not anticipated in these children so the caregivers were taken unaware. This can be worse in infants or in mild cases. Most of the behavioural abnormalities were also associated with the use of prednisolone. There is an urgent need to design guidelines for the management of behavioural abnormalities in nephrotic syndrome especially steroid therapy in resource limited settings. Harmonisation of the skills of paediatric nephrologist and child psychiatrist is also important to obtain the best outcome.